Correction to "Electrocatalyst Performance at the Gas/Electrolyte Interface under High Mass Transport Conditions: Optimization of the 'Floating Electrode'Method" - Lin,X; Zalitis,CM; Sharman,J; Kucernak,A (ACS Applied Materials and Interfaces, 2020)
Due to a production error, an incorrect Supporting Information file was published with this paper. The correct version is included here and has been replaced in the original article.